Trade and the Competitiveness Agenda - Reis, José Guilherme; Farole, Thomas (World Bank, Washington, DC, 2012)
The global economic crisis has forced a major rethinking of the respective roles of governments and markets in the processes of trade and growth. Indeed, industrial policy seems to be back in fashion or, at least, talking about it is. But a renewed 'activism' by government in the trade and growth agenda need not mean a return to old-style policies of import substitution and 'picking winners.' Instead, it may mean a stronger focus on competitiveness by unlocking the constraints to private sector-led growth. This note discusses the renewed role of government in trade and growth policy from the competitiveness angle and it suggests some priorities for the new competitiveness agenda.